2005
DOI: 10.1103/physrevlett.95.051802
|View full text |Cite
|
Sign up to set email alerts
|

Study ofZγEvents and Limits on AnomalousZZγandZγγCouplings in

Abstract: Study of Zγ events and limits on anomalous ZZγ and Zγγ couplings in pp collisions at √ s = 1.96 TeV

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…At tree level in the SM, the individual values of these TGCs are zero. The photon transverse energy spectrum has similar sensitivity to CP-violating and CP-conserving couplings [6]. Therefore, the results are generally interpreted in terms of CP-conserving TGCs h V 3 and h V 4 .…”
Section: Introductionmentioning
confidence: 82%
“…At tree level in the SM, the individual values of these TGCs are zero. The photon transverse energy spectrum has similar sensitivity to CP-violating and CP-conserving couplings [6]. Therefore, the results are generally interpreted in terms of CP-conserving TGCs h V 3 and h V 4 .…”
Section: Introductionmentioning
confidence: 82%
“…Indirect determinations are also in good agreement with the SM value. 23) In addition the leptonic branching ratios of the W, 23) the coupling of the W and Z bosons to photons, [24][25][26] the production of two W or Z bosons, [27][28][29][30] the forwardbackward asymmetry of the Z boson, 31) and several measurements related to the production of W or Z bosons were made.…”
Section: Other Measurements Of W and Z Boson Propertiesmentioning
confidence: 99%
“…The CV4 technique affects both central and autonomous nervous system [ 8 ], assessed by change in the blood flow and in the tissue oxygen saturation [ 9 , 10 ]. Another way to measure the effects of the CV4 technique is the brain cortex electrical activity by electroencephalography (EEG), which is a validated method to support the results [ 11 14 ]. Current literature has only 2 crossover studies with healthy participants: the work of Cutler et al [ 15 ] showed a decrease in sleep latency; and Miana et al [ 16 ] showed an increase in the absolute power of alpha frequency.…”
Section: Introductionmentioning
confidence: 99%